The relationship between urethral mobility and clinical outcomes after midurethral sling surgery - Baihua Zhao; Yali Zuo; Lieming Wen (Continence, 2023)
Objective:: To explore the relationship between urethral mobility and clinical outcomes after midurethral sling (MUS) surgery. Methods:: This was a retrospective analysis of the patients who had MUS surgery and clinic follow-up with ultrasound exams between 2017 and 2022. The sling location, sling-pubic gap (SPG), bladder neck mobility, and segmental urethral mobility were measured and compared between women with cured SUI, recurrent SUI, de novo VD, and continent women without MUS. The correlations between ultrasound findings and clinical outcomes were tested. Results:: Of 198 women with MUS, 176 had a telephone follow-up, and 151 (151/176, 85.8%) were subjectively satisfied. Affected by the epidemic, only 107 patients had clinic follow-up, 92 valid data of 32 cured SUI (Group 1), 37 recurrent SUI (Group 2), and 23 de novo VD (Group 3) were compared with 102 women without MUS. Groups 1 and 2 had significant lower midurethral mobility. In Group 3, the mid and lower urethra was tightly near the symphysis on Valsalva, and the mobility was excessively decreased. SPG was significantly wider in Group 2 than in Group 1 (13.8 ± 3.6 mm vs 11.2 ± 2.7 mm, p = 0.001). SPG was strongly related to midurethral mobility (r=0.32, p=0.002) and clinical outcomes (r=0.45, p<0.001). Multivariable regression showed SPG positively correlated to recurrent SUI [OR: 1.439 (95% CI:1.191–1.738) p<0.001]. Conclusion:: Midurethral sling reduced midurethral mobility. A wider SPG indicated a higher midurethral mobility and a higher risk of recurrent SUI.